2012
DOI: 10.1248/bpb.35.184
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fatty Acid Profile in the Liver of SHR/NDmcr-cp (cp/cp) Rats, a Model of the Metabolic Syndrome

Abstract: The fatty acid profile of hepatic lipid in spontaneously hypertensive rats (SHR)/NDmcr-cp (cp/cp) rats (SHR/NDcp), which offer an animal model of the metabolic syndrome, was characterized by comparing those in Wistar Kyoto rats (WKY), SHR, stroke-prone spontaneously hypertensive rats (SHRSP) and SHR/ NDmcr-cp ( / ) rats (SHR/ND ) . Hierarchical clustering analysis revealed that SHR/NDcp and the other four strains and/or substrains of rats were clearly disparate in fatty acid profile of hepatic lipid and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
5
13
0
Order By: Relevance
“…Moreover, the increased gene expression of LPK suggests that the supply of acetyl-CoA from glucose is also increased in hepatocytes of SHR/NDcp. These results, taken together, strongly imply the increased formation of 16:0 in the liver of SHR/NDcp, a suggestion that is consistent with the previous finding that the liver of SHR/ NDcp contains 16:0 in large quantities [12]. Moreover, the 16:0 produced by FAS may be converted to palmitoyl-CoA by microsomal ACSL, the activity of which in the liver of SHR/NDcp was higher.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the increased gene expression of LPK suggests that the supply of acetyl-CoA from glucose is also increased in hepatocytes of SHR/NDcp. These results, taken together, strongly imply the increased formation of 16:0 in the liver of SHR/NDcp, a suggestion that is consistent with the previous finding that the liver of SHR/ NDcp contains 16:0 in large quantities [12]. Moreover, the 16:0 produced by FAS may be converted to palmitoyl-CoA by microsomal ACSL, the activity of which in the liver of SHR/NDcp was higher.…”
Section: Discussionsupporting
confidence: 91%
“…rats (SHR/ND?) (lean hypertensive littermates of SHR/NDcp), and demonstrated that SHR/NDcp and the other four strains and/or substrains of rats were clearly disparate in terms of fatty acid profile [12]. This disparity was due to drastic increases in the mass of palmitic (16:0), oleic (18:1n-9), palmitoleic (16:1n-7), cis-vaccenic (18:1n-7) and 5,8,11eicosatrienoic (20:3n-6) acids in the liver of SHR/NDcp.…”
Section: Introductionmentioning
confidence: 95%
“…Palmitoleic acid is associated with increased insulin concentrations [55] and resistance [56] [57] [58] [59] [60] [61] [62], type II diabetes [63] [64], metabolic syndrome [61] [65] [66], heart failure [67] and coronary heart disease [68]. Plasma palmitoleic acid content is an independent marker of both triglyceridemia and abdominal adiposity in men [62] [69], which agrees with the positive correlation between this fatty acid peripheral level and the amount of abdominal fat deposition found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, there is scarce information about this issue; nevertheless a previous work reported that a SHR/NIH corpulent rat substrain (SHR/NDcp), which was obtained by crossing SHR/NIH corpulent rat with SHR, shows 5.5 times higher scd1 gene expression than that of WKY but also showed a tendency of the original SHR strain to have decreased levels of Scd1 expression in comparison with WKY rats [28]. …”
Section: Discussionmentioning
confidence: 99%